2005
DOI: 10.1002/j.2162-6057.2005.tb01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Conceptions of Creativity and Creative Students

Abstract: Teachers' conceptions of creativity and creative students were investigated. Questionnaires were administered to elementary school teachers to examine their attitudes, beliefs, and current classroom practices. Teachers were found to possess inaccurate concepts regarding what constitutes creativity and revealed conflicts with the classroom behaviors demonstrated by creative students. The paradox between teachers' reported support for creativity enrichment and virtual lack of related classroom practice is explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
125
3
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(168 citation statements)
references
References 26 publications
5
125
3
16
Order By: Relevance
“…Creativity researchers have shown that teachers from both Western and Eastern cultures are convinced of the importance and role of creativity for the modern world (Aljughaiman & Mowrer-Reynolds, 2005;Westby & Dawson, 1995). In the majority of cases, they associate creativity with creative products (Aljughaiman & Mowrer-Reynolds, 2005), rather than the creative process or creative people (Lee & Seo, 2006;Levenson, 2015;Liu & Lin, 2014;Maksić & Pavlović, 2011;Newton & Beverton, 2012).…”
Section: Creativity Development and Teachers' Beliefs About Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Creativity researchers have shown that teachers from both Western and Eastern cultures are convinced of the importance and role of creativity for the modern world (Aljughaiman & Mowrer-Reynolds, 2005;Westby & Dawson, 1995). In the majority of cases, they associate creativity with creative products (Aljughaiman & Mowrer-Reynolds, 2005), rather than the creative process or creative people (Lee & Seo, 2006;Levenson, 2015;Liu & Lin, 2014;Maksić & Pavlović, 2011;Newton & Beverton, 2012).…”
Section: Creativity Development and Teachers' Beliefs About Creativitymentioning
confidence: 99%
“…Numerous studies suggest that teachers identify creativity with its particular domains, especially with art (i.e., literature, music, visual arts and performing arts) (Aljughaiman & Mowrer-Reynolds, 2005;Kampylis, Berki, & Saariluoma, 2009;Newton & Beverton, 2012). Teachers' focus on artistic domains makes them mainly recognize only those actions and students' creations that are connected with artistic initiative, like drawing, painting, writing, playing musical instruments, dancing or acting.…”
Section: Creativity Development and Teachers' Beliefs About Creativitymentioning
confidence: 99%
“…Examination of the relationship between conceptions and practice showed that the teachers' beliefs, views, and preferences about mathematics and its teaching played a significant, albeit subtle, role in shaping their instructional behavior. To investigate teachers' conceptions of creativity and creative students, Aljughaiman and Mowrer-Reynolds (2005) …”
Section: Teachers' Conceptions Of Creativity In Mathematicsmentioning
confidence: 99%
“…They assembled the ideas about mathematics and about its teaching mathematics. Concerning creativity in mathematics, there have been several studies (e.g., Aljughaiman & Mowrer-Reynolds, 2005;Bolden, Harris, & Newton, 2010;Silver, 1997). Bolden, Harris, and Newton (2010) analyzed pre-service primary teachers' conceptions of creativity in mathematics in the United Kingdom.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation